The Uniqueness of Strong Solutions for the Camassa-Holm Equation. (10th June 2013) - Wu, Meng; Lai, Chong
Abstract : Assume that there exists a strong solution of the Camassa-Holm equation and the initial value of the solution belongs to the Sobolev space H 1 ( R ) . We provide a new proof of the uniqueness of the strong solution for the equation.